Analysis of the Parameters affecting the Signaling System at Coordinated Intersections Case Study - Duman, Zeynep Nur; Murat, Yetis Sazi; Yilmaz, Mehmet (Gazi Univ, 2024)
Population growth, industrialization, and rapid urbanization have led to problems in urban transportation, and different approaches are needed to solve these problems. In this study, three intersections on a sequential corridor with an isolated control system in Elazig province were examined as an example. Traffic volume measurements were taken during peak hours of all days of the week using built-in cameras in this corridor. The existing geometry of the intersections, control forms, signal cycles, phase durations, and phase plans were also considered. The current situation of the intersections was analyzed and evaluated using microsimulation software (PTV Vissim). Offset times were determined by considering the average speed and distances between the intersections, and coordination was established between the intersections. Four different coordinated states were analyzed and evaluated using microsimulation software by making changes to the intersection geometry, phase, and cycle time diagrams. The delay, number of stops, service level, queue lengths, travel time, and average speed parameters were compared between the current situation and the four different coordinated situations created. As a result of the study, it was found that significant improvements (50% or more) were achieved in the performance criteria considered in the situations of coordinated control compared to the current situation, and these improvements had different values for each criterion and situation. Therefore, it was concluded that coordinated control of intersections instead of isolated controls would be beneficial for urban traffic management, and the reorganization of intersection geometries together with the signal timings and phase plans could contribute to corridor management.
Keywords: Traffic; signaling; coordinated intersections; bandwidth; offset